Biplot Analysis of Life Satisfaction Dimensions in the Happiness Index - Bimo Okta Syahputra; Rachma Hikmaya; Nabila Angel Nafisha; Immanuel Alexander Sirait; M. Fariz Fadillah Mardianto; Dita Amelia; Elly Anna (Universitas Airlangga, 2024)
The main goal of every individual in life is to achieve happiness, a subjective concept. To measure happiness, one approach used is the life satisfaction dimension. In multivariate analysis, the biplot method emerges as a useful tool to map variables and objects of observation simultaneously in a two-dimensional graph. This study was conducted with the aim of analyzing biplots on the happiness index, with the dimension of life satisfaction as the main variable. The data used comes from the Central Bureau of Statistics (BPS), specifically related to the Life Satisfaction Dimension of the Happiness Index in 2021. By conducting careful biplot analysis, the pattern of relationships between provinces in the context of happiness can be revealed. The results of the biplot analysis show that provinces in the same quadrant have closer similarities in happiness characteristics than provinces in different quadrants.